ACQUIRED LANGUAGE DISORDERS IN BILINGUALS - Elisa Cargnelutti; Barbara Tomasino; Franco Fabbro (European Medical Journal Neurology, 2019)
The literature reports an increased number of aphasias involving bilingual people. Dealing with bilingual aphasia requires particular attention from the diagnostic to the therapeutic phase. In this review, the authors describe the possible impairment patterns, which could be different between the two languages and be characterised by specific deficits and sometimes unexpected profiles. The role of some crucial factors in determining the observed deficits and impairment patterns is illustrated, for instance age of appropriation and proficiency. An early versus late language appropriation recruits different brain processes and hence different brain structures. In general, a greater vulnerability is observed for the late-learned languages, although a high proficiency or use and exposure appear to prevent language impairment even in the case of late appropriation. The authors also discussed the role of other intervening factors, such as emotional–motivational aspects, which could explain unusual profiles. Furthermore, language deficits specific to bilingualism, such as pathological mixing and switching and translation problems were described. In this respect, the authors underlined the fundamental involvement of cognitive control mechanisms and of the role of the brain structures associated with this. Lastly, the clinical practice issues in bilingual aphasia were outlined, underlining the need for a careful diagnosis. This should take into account the patient’s language history in order to avoid biased assessments and instead promote the setup of effective intervention programmes.